2018
DOI: 10.3389/fphys.2018.01112
|View full text |Cite
|
Sign up to set email alerts
|

The Amphibious Mudskipper: A Unique Model Bridging the Gap of Central Actions of Osmoregulatory Hormones Between Terrestrial and Aquatic Vertebrates

Abstract: Body fluid regulation, or osmoregulation, continues to be a major topic in comparative physiology, and teleost fishes have been the subject of intensive research. Great progress has been made in understanding the osmoregulatory mechanisms including drinking behavior in teleosts and mammals. Mudskipper gobies can bridge the gap from aquatic to terrestrial habitats by their amphibious behavior, but the studies are yet emerging. In this review, we introduce this unique teleost as a model to study osmoregulatory b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 192 publications
(278 reference statements)
0
15
0
Order By: Relevance
“…On land, mudskippers continually search for water (Supplementary Video S1), in much the same way as tetrapods [16]. Indeed, we recently demonstrated that artificial removal (e.g., by piercing holes in the opercula) of buccal water stored on land by the mudskipper resulted in a strong behavioral preference for a water environment, suggesting the presence of thirst (defined as a conscious sensation of a need for water and a desire to drink, which is followed by a search for water in terrestrial animals such as mammals [29,30]) in fish [17].…”
Section: Migration To Water Motivated By Local Sensation In the Buccamentioning
confidence: 99%
See 3 more Smart Citations
“…On land, mudskippers continually search for water (Supplementary Video S1), in much the same way as tetrapods [16]. Indeed, we recently demonstrated that artificial removal (e.g., by piercing holes in the opercula) of buccal water stored on land by the mudskipper resulted in a strong behavioral preference for a water environment, suggesting the presence of thirst (defined as a conscious sensation of a need for water and a desire to drink, which is followed by a search for water in terrestrial animals such as mammals [29,30]) in fish [17].…”
Section: Migration To Water Motivated By Local Sensation In the Buccamentioning
confidence: 99%
“…The factors such as stressors driving many amphibious fish to water have been reviewed, and these factors can also be triggered in cyprinodontiforms, including in model species (e.g., Kryptolebias marmoratus) [105,106]. The mode of action can be assessed through neurohistological methods of labeling of Fos and neuro/endocrine transmitter systems in the less complicated fish brain [16], since these species have sequenced genomes [7,[107][108][109].…”
Section: Summary and Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, studies in aquatic amphibious fishes revealed a unique system of Ang II-related thirst regulation. In mudskipper, Ang II stimulates the area postrema (AP), a hindbrain nucleus, to induce swallowing action [17,18]. Recent studies with contemporary neural manipulation tools have expanded our knowledge of thirst circuits at a finer resolution.…”
Section: Driving Of Thirst Thirst Driving System Across Species and Gmentioning
confidence: 99%